ANALISIS PERENCANAAN STRATEGI DALAM MENINGKATKAN PENGEMBANGAN USAHA PUSAT BELAJAR MASYARAKAT (PKBM) RUMAH HIJAU KABUPATEN DELI SERDANG SUMATERA UTARA - Andika, Rindi (Universitas Negeri Medan, 2022)
The strategic planning of the Community Learning Activity Center (PKBM) is the main function of management in the fields that include planning, organizing, implementing and supervising. This study aims to analyze the improvement in the development of the Green House Community Learning Activity Center (PKBM). The type of research used in this study is a qualitative research with a descriptive type of research that is not intended to test certain hypotheses but to find an overview of the strategic planning of the Community Learning Activity Center (PKBM). The data and information needed in this study were obtained from information from informants, namely people who are considered to know and can be trusted in providing accurate information using two types of data, namely primary data and secondary data. Data collection techniques in this research are direct observation to the research site, in-depth interviews and documentation at the research site. The results of the research show that the implementation of the four management functions of the Green House Community Learning Activity Center (PKBM) when viewed from the planning function is categorized as good because it is structured. The organizing or grouping function is categorized as good, because there are no specific rules, then in the process of implementing the Community Learning Activity Center (PKBM) it is carried out from Monday to Friday, then the supervisory function where during learning activities is supervised by supervisors from the Deli Serdang Education Office.